The Philosophical Basis of the Supervisory Function of the House of Representatives on the Implementation of the State Revenue and Expenditure Budget - Jaidun; Slamet Suhartono; Hufron; Syofyan Hadi (Technium Social Sciences Journal, 2022)
The purpose of this study is to analyze and find the philosophical basis for the supervisory function of the House of Representatives on the implementation of the State Revenue and Expenditure Budget. The research uses normative legal research methods that entirely use secondary data. Based on the study, it was found that the philosophical basis for supervision of the House of Representatives against the Government (Executive) on the implementation of the State Revenue and Expenditure Budget, among others, aims to: (1) prevent the concentration of power (centralization of power) in one branch of Executive power (Government), (2) prevent abuse of government power (abuse of power), (3) preventing fraud/deviation, (4) controlling and limiting the power of the government (executive), (5) exercising people’s sovereignty, (6) mutual supervision among state institutions, (7) realizing good government (good governance), (8) preventing state financial losses (State Revenue and Expenditure Budget) from corruption, (9) opening access to public information (transparency) as widely as possible so that the public is involved in direct supervision against the Government (Executive) for the implementation of the State Revenue and Expenditure Budget.